Smoothed Analysis of Belief Propagation for Minimum-Cost Flow and Matching - Brunsch, Tobias; Cornelissen, Kamiel; Manthey, Bodo; Röglin, Heiko (Journal of Graph Algorithms and Applications, 2013)
Belief propagation (BP) is a message-passing heuristic for statistical inference in graphical models such as Bayesian networks and Markov random fields. BP is used to compute marginal distributions or maximum likelihood assignments and has applications in many areas, including machine learning, image processing, and computer vision. However, the theoretical understanding of the performance of BP remains limited. Recently, BP has been applied to combinatorial optimization problems. It has been proved that BP can be used to compute maximum-weight matchings and minimum-cost flows for instances with a unique optimum. The number of iterations needed for this is pseudo-polynomial and hence BP is not efficient in general. We study BP in the framework of smoothed analysis and prove that with high probability the number of iterations needed to compute maximum-weight matchings and minimum-cost flows is bounded by a polynomial if the weights/costs of the edges are randomly perturbed. To prove our upper bounds, we use an isolation lemma by Beier and Vöcking (SIAM Journal on Computing, 2006) for the matching problem and we generalize an isolation lemma by Gamarnik, Shah, and Wei (Operations Research, 2012) for the min-cost flow problem. We also prove lower tail bounds for the number of iterations that BP needs to converge that almost match our upper bounds.